Silent cardiac tumor with neurological manifestations. Issue 4 (April 2017) - Gil, Júlio; Marmelo, Bruno; Abreu, Luís; Antunes, Hugo; dos Santos, Luís Ferreira; Cabral, José Costa
Abstract: Atrial myxoma is rare and can be completely asymptomatic. However, an untreated myxoma may result in catastrophic events. Diagnosis is usually suggested by echocardiography, and other imaging modalities can add important information. Myxoma can be cured surgically, and histological analysis usually gives the definite diagnosis. This article describes the case of a 61-year-old woman whose clinical presentation of an atrial myxoma was a stroke. Echocardiographic findings were highly suggestive of a cardiac myxoma. However, cardiac magnetic resonance showed unusual features for myxoma, since the mass was hyperintense in T1-weighted images and hypointense in T2-weighted sequences. Histology confirmed myxoma and the patient was surgically treated. This case enhances the importance of multimodality imaging in the differential diagnosis of cardiac masses. <Learning objective: This case report describes a patient presenting with a stroke. Echocardiography demonstrated an atrial mass, suggestive of a cardiac myxoma. Cardiac magnetic resonance revealed a mass with unusual features for a myxoma, namely hyperintensity in FSE-T1 and hyposignal in FSE-T2. The authors make a brief summary of the neurological manifestations and imaging characteristics of the atrial myxoma. The importance of multimodality imaging in the diagnosis of cardiac tumors is also discussed.>